Evolving Mechanism of Eutectic Carbide in As-cast AISI M2 High-speed Steel at Elevated Temperature - 周滨 申昱 陈军 崔振山 (Shanghai jiao tong da xue xue bao, 2010)
The evolution in type, size and shape of carbides in as-cast American Iron and Steel Institute （AISI） M2 high-speed steel before and after annealing were investigated. The micromechanism which was responsible for those changes was also analyzed and discussed. At the initial stage of reheating, metastable M2C-type carbide decomposed continuously. M6C-type carbide nucleated at the interface of M2C/γ firstly and grow from surface to center. Then MC-type carbide nucleated at both surface of M6C/M6C and inner of M6C. With the increasing decomposition of the metastable M2C-type carbide, the rod-shaped construction of eutectic carbide began neck- ing, fracturing and spheroidizing gradually. Held enough time or reheated at higher temperature, particle-shaped product aggregated and grew up apparently, while secondary carbide precipitated in cell and grew up less sig- nificantly than the former. Based on the above microstructural observation, the thermodynamic mechanism for decomposition of M2C carbide, for spheroidization of products, and for the growth of particles were analyzed. The rate equations of carbides evolution were derived, too. It shows that the evolving rate is controlled by diffusion coefficients of alloy atoms, morphology of eutectic carbides and heating temperature.